Clinical Characteristics and Treatment Outcome of Peginterferon Plus Ribavirin in Patients Infected with Genotype 6 Hepatitis C Virus in Korea: A Multicenter Study - Shin, Su Rin (Gut Liver, 2017)
BACKGROUND/AIMS: Because of the limited geographic distribution, there have been insufficient data regarding hepatitis C virus (HCV) genotype 6 in Korea. This study aimed to investigate the clinical characteristics and available treatment outcomes of patients with genotype 6 HCV in Korea. METHODS: From 2004 to 2014, data were collected from Korean patients infected with genotype 6 HCV in eight hospitals. RESULTS: Thirty-two patients had genotype 6 HCV. The median age was 44 years, and 6c was the most common subtype. The baseline median alanine transaminase level was 88 (21 to 1,019) IU/mL, and the HCV RNA level was 1,405,000 (96,500 to 28,844,529) IU/mL. Twenty-five patients were treated with peginterferon (PEG-IFN) and ribavirin. Three follow-up losses occurred. Additionally, 13 patients attained a sustained virologic response (SVR), seven patients relapsed, and two patients exhibited a null response. The SVR rates were 40% and 75% for the 24- and more than 48-week treatments, respectively, and five of the six patients who achieved a rapid virologic response (RVR) attained a SVR. CONCLUSIONS: Korean patients infected with genotype 6 HCV are relatively young, and 6c is the most common subtype. When treated with PEG-IFN and ribavirin, the SVR rate was 52%. Similar to other genotypes, a longer duration of treatment and attainment of RVR are important for SVR.